International webinar and training for inbound and outbound students, Faculty of Pharmacy, UiTM / Hanish Singh Jayasingh Chellammal ... [et al.] - Chellammal, Hanish Singh Jayasingh (Faculty of Pharmacy, 2024)
These webinar programmes were conducted by the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam, in collaboration with the Vels Institute of Science, Technology & Advanced Studies (VISTAS), Chennai, India; Queen’s University Belfast (QUB), Ireland, UK; and Gandhi Institute of Technology and Management (GITAM) University, Hyderabad, India. Both the programmes, inbound and outbound, were part of each one-day webinar.